Biological, material and socio-cultural constraints to effective menstrual hygiene management among secondary school students in Tanzania. - Dani Stoilova; Rebecca Cai; Sandra Aguilar-Gomez; Naomi Heller Batzer; Elias Charles Nyanza; Anja Benshaul-Tolonen (Public Library of Science (PLoS), 2022)
Menstrual hygiene management is an important determinant for girls' educational outcomes. We develop a method of cross-sectional analysis that quantifies the relative importance of four distinct mechanisms: material, biological, social and informational constraints and consider four main schooling outcomes: absenteeism, early departure, concentration and participation. We use survey data from 524 female students enrolled in four co-educational secondary schools in Northern Tanzania. Average age at first period is 14.2 years (standard deviation = 1.1, range 9-19). Information is the least binding constraint: 90-95% of girls report they received information about menstruation and how to manage it. In contrast, biological constraints are hindering: (i) the distribution of menstrual cramps and pain is bifurcated: most girls report very light or very strong pain (rather than moderate) with considerable educational impacts for girls in the latter group, (ii) irregular cycles (62%) and difficulty predicting the cycle (60%) lead to stress and uncertainty. Socio-cultural constraints are binding as 84% would feel shame if male peers knew their menstrual status, and 58% fear being teased over periods. Material constraints include prohibitive costs: girls spending between 12-70% of the daily national poverty line (6,247 TSH per day) on pads during their period. However, we discern no statistically significant relationship between access to pads and absenteeism. In contrast, biological and socio-cultural constraints as well as lack of sanitary infrastructure have significant effects on absenteeism. The results have several implications. First, sanitary pad interventions should consider participation and concentration as main outcomes, in addition to absenteeism. Second, biological (menstrual cramps and pain) and socio-cultural (fear, stigma) constraints are drivers of menstruation-related absenteeism and participation in the classroom and need to be evaluated in trials. We suggest exploring analgesic use, alternative pain-management techniques, menstrual cycle tracking technologies, and social programming in future trials.